Convergence in total greenhouse gas emissions worldwide - Ignacio Belloc; José Alberto Molina (Global Labor Organization (GLO), 2023)
This paper examines convergence patterns in total greenhouse gas emissions across 114 countries from 1990 to 2019. Prior research has largely focused on one representative greenhouse gas, carbon dioxide emissions, but our goal is to broaden the study. We use the club convergence test to contrast the null hypothesis of convergence for a pool of data and identify subgroups of convergence. The results reveal different clubs according to the air pollutant considered, indicating the importance of considering a range of air pollutants in convergence analyses. We also explore the main determinants of the observed convergence patterns and estimate various ordinal models. We find that income level, urbanization, natural resources dependency, renewables energy consumption, trade openness, and corruption level all contribute to explain these different patterns. Our determinant analyses especially note the importance of institutional quality. The results are important in reformulating current environmental policies, which are mostly based on the hypothesis of overall convergence, according to the different convergence clubs detected.
Keywords: C23; O47; O50; Q53; 330; greenhouse gas emissions; convergence; global analysis; environmental policy; institutions